2014
DOI: 10.4253/wjge.v6.i11.555
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissectionvsendoscopic mucosal resection for early gastric cancer: A meta-analysis

Abstract: In the endoscopic therapy of EGC, ESD showed a superior efficacy but higher complication rate with respect to EMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 27 publications
2
86
0
3
Order By: Relevance
“…[2][3][4] In our review, bleeding after ESD occurred in 5.1% of all procedures. We believe this is the best estimate for PPB because all studies included were selected only if a clear definition of PPB was provided and reported separately from intraprocedural bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In our review, bleeding after ESD occurred in 5.1% of all procedures. We believe this is the best estimate for PPB because all studies included were selected only if a clear definition of PPB was provided and reported separately from intraprocedural bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…ESD showed a superior efficacy with respect to endoscopic mucosal resection in a recent meta-analysis[3]. As adoption of this procedure becomes ever more widespread, the indications for endoscopic therapy are being expanded[4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for gastric cancer include endoscopic treatment, surgery, chemotherapy and radiation (1,3,4). Key types of endoscopic treatment include endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) (5,6). Despite improvements in treatment efficacy, prognoses for gastric cancer remain poor (7).…”
Section: Introductionmentioning
confidence: 99%